2014
DOI: 10.3354/meps10687
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hatching seawater pCO2 affects development and survival of zoea stages of Arctic spider crab Hyas araneus

Abstract: The sensitivity of marine crustaceans to anthropogenic CO 2 emissions and the associated acidification of the oceans may be less than that of other, especially lower, invertebrates. However, effects on critical transition phases or carry-over effects between life stages have not been comprehensively explored. Here we report the impact of elevated partial pressure of CO 2 (pCO 2) values (3100 µatm) in seawater on Hyas araneus during the last 2 wk of their embryonic development (pre-hatching phase) and during de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Our results showed that OA has a mixed effect on swimming crabs, with increased survival and retarded growth. The negative effect on growth is in line with findings published for other crab species such as larvae of H. araneus ( Walther et al, 2010 ; Schiffer et al, 2013 , 2014 ; Wang et al, 2018 ), Paralithodes camtschaticus , and Chionoecetes bairdi ( Long et al, 2013a , b ), as well as embryos of Petrolisthes cinctipes ( Carter et al, 2013 ; Ceballos-Osuna et al, 2013 ). Such a consensus between studies performed on different species, at different stages of development and with p CO 2 ranging from 710 to 3100 μatm, strongly supports crab sensitivity to OA.…”
Section: Discussionsupporting
confidence: 89%
“…Our results showed that OA has a mixed effect on swimming crabs, with increased survival and retarded growth. The negative effect on growth is in line with findings published for other crab species such as larvae of H. araneus ( Walther et al, 2010 ; Schiffer et al, 2013 , 2014 ; Wang et al, 2018 ), Paralithodes camtschaticus , and Chionoecetes bairdi ( Long et al, 2013a , b ), as well as embryos of Petrolisthes cinctipes ( Carter et al, 2013 ; Ceballos-Osuna et al, 2013 ). Such a consensus between studies performed on different species, at different stages of development and with p CO 2 ranging from 710 to 3100 μatm, strongly supports crab sensitivity to OA.…”
Section: Discussionsupporting
confidence: 89%
“…Reduced pH has been suggested to negatively impact the survival of red king crab embryos and larvae (Long et al ., 2013 a ) as well as embryos and larvae of other crabs (Carter et al ., 2013; Ceballos-Osuna et al ., 2013; Schiffer et al ., 2014 b ). Results of transcriptomic analyses presented in this study strongly suggest that wide variation in environmental pH largely does not influence regulation of gene expression in late embryos/newly hatched larvae or in the expression of genes in larvae following 7–8 days of exposure to reduced environmental pH (Table 1, Figures 3 & 4).…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen consumption rates (MO 2 ) of late-stage embryos (at 50% eye pigmentation) were measured in closed, temperature-controlled respiration chambers (OXY0 41 A, Collotec Meßtechnik GmbH, Germany, Supplementary Fig. S2 ) following methodologies described by Schiffer et al (2014) . All measurements were performed in duplicates (with two respiration chambers) at the same developmental stage (~50% eye pigmentation) and treatment as during incubation.…”
Section: Methodsmentioning
confidence: 99%